Language vitality of Acehnese: Survey results and factors affecting its sustainability - Iskandar Syahputera; Berlin Sibarani; Masitowarni Siregar (Universitas Syiah Kuala, 2026)
This study investigates the vitality status of the Acehnese language and factors affecting its sustainability, drawing connections to SDG 4 (Quality Education; literacy). Employing a quantitative survey design, data were collected from 598 respondents across five districts of Aceh Province, Indonesia, using multi-stage cluster random sampling. The study applied a modified UNESCO 2003 Language Vitality Assessment framework comprising seven factors: intergenerational transmission, domain trends, response to new domains and media, availability of written materials for education, governmental support, community attitudes, and documentation quality. Data analysis using SPSS determined the endangerment level on UNESCO’s six-point scale. Findings reveal that Acehnese vitality is at Level 3 (definitely endangered), with intergenerational transmission identified as the most critical factor contributing to decline. This decline directly undermines SDG Target 4.6, as mother-tongue literacy is foundational for achieving functional literacy among Acehnese youth. Without intergenerational transmission, universal literacy in Acehnese becomes unattainable, and lifelong learning pathways are disrupted from early childhood. While older generations continue speaking Acehnese, transmission to younger speakers is weakening significantly. Among seven factors, only governmental support (Factor 5) was rated “safe.” Other factors ranged from definitely to severely endangered, reflecting limited use of the educational domain, minimal digital media presence, inadequate written materials for mother-tongue literacy instruction, mixed community attitudes, and insufficient documentation. The study concludes that without strategic intervention targeting SDG targets, including mother-tongue literacy programs, accessible Acehnese learning materials, and formal recognition in foundational education, the language faces further decline, risking equitable quality education for Acehnese-speaking communities.